Stroke in right dorsal anterior insular cortex Is related to myocardial injury. Issue 4 (3rd April 2017) - Krause, Thomas; Werner, Kathrin; Fiebach, Jochen B.; Villringer, Kersten; Piper, Sophie K.; Haeusler, Karl Georg; Endres, Matthias; Scheitz, Jan F.; Nolte, Christian H.
Abstract : Objective: Elevated levels of cardiac troponin, and especially their relative changes over time, indicate acute myocardial injury. They are also frequently observed after acute ischemic stroke (AIS), indicating poor functional outcome and increased mortality. However, recent evidence showed that, in most AIS patients, myocardial injury is not caused by coronary ischemia. Instead, stroke lesion location has been suggested to precipitate myocardial injury. Methods: Voxel‐based lesion‐symptom mapping (VLSM) was used in 299 patients who had a magnetic resonance imaging–confirmed acute ischemic stroke within the anterior circulation and a high‐sensitivity cardiac troponin T (hs‐cTnT) acquired on the day of admission. Of these, 228 had a second troponin measurement during the acute phase. The absolute hs‐cTnT levels above the 99th percentile of a healthy reference population (≥14ng/l) as well as their relative temporal changes were used as continuous variables of interest in the VLSM model, including a multiple regression analysis adjusted for confounding variables. Results: The anterior insular cortex of the right hemisphere, in particular its dorsal subregion, was significantly associated with the relative temporal changes of hs‐cTnT ( p  < 0.01, corrected for multiple comparisons). In contrast, the baseline hs‐cTnT levels on admission were not related to lesion location anywhere within the anterior circulation. Interpretation: Our results amplify recent evidence from functional neuroimaging, which suggests a prominent role of dorsal anterior insular cortex in the parasympathetic control of cardiac and autonomic function. Acute vascular damage of this insular subregion might lead to autonomic dysbalance and an upregulation of sympathetic function, thereby resulting in myocardial injury. Ann Neurol 2017;81:502–511